Susceptibility of Epithelial Cells to Pseudomonas aeruginosa Invasion and Cytotoxicity Is Upregulated by Hepatocyte Growth Factor - Fleiszig, Suzanne M. J. (American Society for Microbiology, 1998)
Normal cell polarity protects epithelial cells against Pseudomonas aeruginosa invasion and cytotoxicity. Using epithelial cell clones with selective defects in sorting of membrane constituents, and using hepatocyte growth factor pretreatment, we found that polarized susceptibility to P. aeruginosa can be altered without disrupting tight junctions. The results also showed that cellular susceptibility factors for invasion and cytotoxicity are not the same, although both are localized to the basolateral cell surface in polarized epithelial cells.